Regional cerebral tissue oxygen saturation changes following blood transfusion in neuro‐intensive care unit patients – a pilot observational study. Issue 4 (10th January 2018) - Muthuchellappan, R.; Shaikh, N. A.; Surve, R. M.; Ganne, U. R. S.; Philip, M.
SUMMARY: Background: Although central venous oxygen saturation (ScvO2 ) is used to decide on red blood cell (RBC) transfusion, whether its improvement is associated with parallel improvement in cerebral oxygenation is not adequately studied. This study looked at changes in regional cerebral tissue oxygen saturation (rSO2 ) following RBC transfusion in neuro‐intensive care unit (ICU) patients. Methods: In this prospective observational pilot study, rSO2 was measured in adult neuro‐ICU patients before RBC transfusion, at the end and at 6, 12, 18 and 24 h after RBC transfusion. rSO2 measurements were taken using cerebral oximetry on both sides of the hemicraniums. Haemoglobin, central venous pressure, ScvO2 and temperature were recorded during the study period. Arterial oxygen content, central venous oxygen content and cerebral fractional oxygen extraction were calculated. Mann Whitney U test was used to study the changes in variables at baseline and at 24 h following RBC transfusion. Friedman's test was used to study changes in parameters from baseline to 24 h post‐transfusion. A P value of <0·05 was considered to be significant. Results: The data from 13 subjects were analysed. rSO2 increased significantly following RBC transfusion on both sides of the brain ( P  = 0·002, P  = 0·007), with a corresponding decrease in cerebral fractional oxygen extraction ( P  = 0·001, P  = 0·007). Conclusions: RBC transfusion increased rSO2 significantly on both sides of the brain. As patients' outcomes were not studied, whether this increase in regional cerebral oxygen saturation is beneficial or if it is because of excess DO2 is still unclear. Further studies are required to clarify this issue.